ANALISIS RISIKO RANTAI PASOK KOPI GREEN BEAN DENGAN MENGGUNAKAN METODE HOUSE OF RISK (Studi Kasus di PTPN XII Kebun Silosanen) - Dinda Paramudita; Ida Bagus Suryaningrat (AGROINTEK, 2022)
PTPN XII Silosanen is one of the large state-owned coffee plantations (PBN) in East Java Province. PTPN XII Silosanen in running its business encountered several problems. One of them is the raw material produced is low. This has the potential to cause the production target not to be achieved, so the company is unable to meet consumer demand. These problems will cause losses for the company, so efforts must be made to prevent the occurrence of risks. This study aims to identify risk events and sources of risk, as well as develop treatment strategies to minimize the occurrence of risks. The method used is the House of Risk (HOR) method. The HOR method consists of two phases. HOR phase 1 is used to identify risk events and sources of risk, while HOR phase 2 is used to develop risk management strategies. The results of this study indicate that there are 26 risk events and 28 sources of risk, and 15 strategies for handling risk sources are obtained. Furthermore, 7 priority treatment strategies are obtained to mitigate risk events.